Unclamped Hand-Assisted Laparoscopic Partial Nephrectomy for Predominantly Endophytic Renal Tumors - Engel, Jason D; Williams, Stephen B (Urology Journal, 2013)
PURPOSE: To describe our initial experience with unclamped laparoscopic hand-assisted partial nephrectomy for predominantly endophytic renal masses in the setting of relative contraindication to warm ischemia. MATERIALS AND METHODS: Unclamped laparoscopic hand-assisted partial nephrectomy was performed on eight consecutive patients from June 2009 to March 2010. All patients had predominantly endophytic renal masses with a preferential enhancing rim noted on the pre-operative computed tomography. The unclamped hand-assisted approach was utilized for no warm ischemia, minimal blood loss, and enhanced visualization of the tumor bed with improved operative exposure. RESULTS: Mean age of the participants was 55.8 years. All patients underwent unclamped hand-assisted partial nephrectomy (ie, zero ischemia). Mean estimated blood loss was 368.8 cc (range, 100 to 800 cc) and mean operation time was 236.9 minutes (range, 175 to 272 minutes). There were no intra-operative complications and no open conversions. There was one grade II (ileus with small pneumothorax) and one grade IV (pulmonary embolism) in the 90-day peri-operative period. There was one positive surgical margin, which was recognized intra-operatively. CONCLUSION: While our results are preliminary, we feel this technique provides superior visualization and adequate hemostasis while preserving oncologic efficacy and renal function in this patient population.